Adaptation of the Traditional Randai Performing Art into an Ethno-Fiction Film Scenario: The Story of 'Panyamun' - Muhammad Jel Fadjri Matenas; Yusril (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
Randai is a traditional Minangkabau performing art based on storytelling that combines elements of dance, martial arts, singing, and traditional music. The strength of Randai lies in its oral narration, rhythmic dialogue, and improvisation by the performers. This is what makes Randai attractive for adaptation into an ethno-fiction film script. Ethno-fiction film is an ethnography-based cinematic approach that is fictional in nature, combining cultural observation methods with artistic dramatisation. This paper discusses the concept, adaptation process, and application of Sapardi Djoko Damono's method in transforming the Randai Panyamun story into a film script, rather than a finished film. This study finds that translating the narrative elements of Randai into a screenplay requires a strategy of narrative deconstruction, re-contextualisation of characters, and visual dramaturgical adjustments. The resulting screenplay retains the essence of Randai but is transformed into a cinematic ethno-fiction narrative.